On the issue of modernization of the system of professional development of teachers of high schools of kazakhstan - S.A, Nurgaliyevа; S.Zh., Zeynolla; A.N, Galiyeva; G.K., Espolova (Opción, 2018)
The relevance of the study argued (further) the ongoing modernization of the training of teaching staff as a mechanism for the formation of the new competences of the teacher of high school, the formation of new goals, values and ways of vocational teaching and administrative activity, as well as the need to maintain the country's competitiveness in the education sector. Currently, higher education institutions are also interested in professional development of teachers, because teachers increased ability to adapt to changing social and economic conditions.